BETA AMYLOID POLYCLONAL ANTIBODY IMMUNOGENICITY AS EARLY DEVELOPMENT STUDY OF EARLY DIAGNOSIS FOR ALZHEIMER’S DISEASE - Indra, Muhamad Rasjad; Marhaendraputro, Eko Arisetijono; Hidayat, Rudi Rakhmad (Malang Neurology Journal, 2017)
Background. Alzheimer's disease is a progressive neurologic disease of the brain that triggers irreversible neuronal cell loss, which can interfere with social and occupational functioning. The theory of ACH (Amyloid Cascade Hypothesis) states there are deposits and misfolding of beta amyloid protein thus lead to the formation of plaques and tangles in neurons cells.Objective. To identify the immunogenicity of beta amyloid polyclonal antibodies that can be developed as a first step early diagnosis of Alzheimer's disease.Methods. Rrandomized group post test only design conducted on rabbits. Blood samples were taken from rabbits that had been injected antigen once a week for 5 weeks. Variables were found in this study is the formation of beta amyloid polyclonal antibody with detection levels using dot blot and ELISA methods.Results. It has been reproduced specific polyclonal antibody beta amyloid which has been evidenced by the bond between the antigen with the antibody in a dot blot.Conclusion. The beta amyloid antibodies can be produced through production techniques with a polyclonal antibody against beta amyloid antigen induced rabbit.